Effects of different boiling and stir-fried with bran processes on chemical composition of Pueraria lobata - Tang, Mao-Cheng; Song, Xin-Ying; Huang, Wei; Lu, Xiang-Yang; Wang, Chong; Liu, Hu-Hu (Frontiers in Nutrition, 2025)
BackgroundPueraria lobata has a long edible history owing to its special physiological activities. However, research on the processing methods for P. lobata is limited.MethodsIn this study, a more suitable boiling process was established by optimizing the heating method, solvent selection, and different processing techniques. In addition, the stir-fried with bran method was used to investigate the changes in heavy metal contents in P. lobata.ResultsCompared with the traditional process, the heavy metal content was reduced 96.5% and the isoflavone content was increased 7.5% in the decoction obtained by continuous heating with a ratio of water-to-white wine of 10:1. Meanwhile, we explored the effect of different stir-fried with bran processes on the reduction of lead, cadmium, chromium, copper, and arsenic in P. lobata. The results showed that the use of medium heat for 20 s and 30% bran roasting for 1 min resulted in the lowest overall heavy metal content in P. lobata.ConclusionThis study will provide the reference for reducing heavy metals from P. lobata using different processing methods.